книжная торговля в сибири в условиях постсоветского развития (90-е гг. xx в. - начало xxi в.) (Библиосфера, 2010)
The article describes the transformation of Siberian book trade as a part of the Russian book market at the turn of the centuries (1991-2008). The main tendencies of the transition from the united centralized state system to a multi-market one are identified. Stage-by-stage transforma-tion of the book trade system and its individual components revealed in the consequent changes of its structure, forms and methods.